Traffic noise measurements in antwerp and brussels and their relation with annoyance - MYNCKE, H.; COPS, A.; GAMBART, R.; STEENACKERS, P. (Archives of Acoustics, 1979)
This work is a part of a large scale traffic noise survey in two Belgian cities: Antwerp and Brussels.A social survey (interviews of 1800 persons) was coupled with intensive acoustical measurements (40 places in Antwerp and 25 in Brussels, covering 1100 hours of measurements). Part I concerns the physical measurements, analysis and synthesis of the data. A prediction method based on these measurements is also included. Part II concerns the results of the enquiry about annoyance and its correlation with physical quantities.